The Effect Of Perceived Usefulness, Perceived Security Risk, Perceived Privacy Risk, And Perceived Ease Of Use On Trust And Usage Intention Of The Grabfood Dine-Out Deals Feature In Indonesia - Maria Yohana Siregar; Mahrinasari MS; Roslina (International Journal of Economics, Business and Innovation Research, 2026)
The accelerated integration of digital technology into everyday consumer activities has transformed how individuals engage with food service platforms in Indonesia. One of the innovations introduced by Grab is the GrabFood Dine-Out Deals (DOD) feature, which enables users to purchase promotional dining vouchers directly through the application and redeem them at partner restaurants. Despite its functional benefits, user adoption of this feature remains limited, prompting questions regarding the determinants of users’ trust and behavioral intention. This study examines the influence of Perceived Usefulness, Perceived Security Risk, Perceived Privacy Risk, and Perceived Ease of Use on Trust and Usage Intention of the DOD feature. A quantitative approach was employed with 300 respondents meeting predetermined criteria. Structural Equation Modeling via SmartPLS was used for hypothesis testing. Empirical results show that Perceived Ease of Use, Perceived Security Risk, and Perceived Privacy Risk exert significant effects on Trust, whereas Perceived Usefulness does not. Furthermore, Trust and Perceived Ease of Use significantly influence Usage Intention. The findings underscore that users emphasize safety, privacy assurance, and ease when evaluating dine-in promotional technologies.